Oikophobia and not being at home: educational questions. Issue 6 (2nd November 2021) - Suissa, Judith
ABSTRACT: In this paper, I explore some of the ways in which the notion of 'home' has been invoked in the context of ideas about belonging and nationalism in the wake of the recent EU Referendum in Britain. I focus particularly on Roger Scruton's account of 'oikophobia', and explore some ways in which, while questioning the pathologisation of 'not belonging' implied in Scruton's account, we can nevertheless put the notion of 'home' and its political significance at the heart of our discussions about the educational response to contemporary debates on belonging, migration and movement.